Beban Ganda: Kondisi Perempuan Pemulung pada Masa Pandemi di Tempat Pengolahan Sampah Monang Maning, Denpasar - Bambang Dharwiyanto Putro (Jurnal Kajian Bali (Journal of Bali Studies), 2020)
The Covid-19 pandemic has devastated Bali's economy which relies on the tourism sector. The impact is felt in the informal sector, including scavengers, especially women scavengers who depend on garbage piles. The double burden position they have been doing so far has been exacerbated by the presence of the Covid-19 pandemic. This paper analyzes the condition of women scavengers at TPST Monang Maning, Denpasar, in their roles in the domestic and public spheres and reveals the implications during the pandemic. This research uses observation, interview and literature techniques. This paper uses an approach to the function of women in the domestic and public sphere and a subaltern study approach to see the implications of the double burden of women scavengers’s phenomenon during the pandemic. The results showed that the double burden phenomenon experienced by women scavengers was increasingly burdensome during the pandemic. Limited space for movement in the public sphere and additional burdens in the domestic sphere have implications for their position as a subaltern or dominated group. The patriarchal culture that led them to a subaltern position grew stronger during the pandemic.